Job Turnover, Wage Rates, and Marital Stability : How Are They Related? - Avner Ahituv; Robert I. Lerman (Institute for the Study of Labor (IZA), 2005)
This study examines the interplay between job stability, wage rates, and marital instability. We use a Dynamic Selection Control model in which young men make sequential choices about work and family. Our empirical estimates derived from the model account for selfselection, simultaneity and unobserved heterogeneity. The results capture how job stability affects earnings, how both affect marital status, and how marital status affects earnings and job stability. The study reveals robust evidence that job instability lowers wages and the likelihood of getting and remaining married. At the same time, marriage raises wages and job stability. To project the sequential effects linking job stability, marital status, and earnings, we simulate the impacts of shocks that raise preferences for marriage and that increase education. Feedback effects cause the simulated wage gains from marriage to cumulate over time, indicating that long-run marriage wage premiums exceed conventional short-run estimates.
Keywords: J31; J63; C33; C15; J12; 330; marriage and marital dissolution; job turnover; wage rates; panel data; Ehe; Familienökonomik; Arbeitsplatzsicherung; Arbeitsmobilität; Lohn; Erwerbsverlauf; Schätzung; Vereinigte Staaten